A horizon scan of global conservation issues for 2015. (January 2015) - Sutherland, William J.; Clout, Mick; Depledge, Michael; Dicks, Lynn V.; Dinsdale, Jason; Entwistle, Abigail C.; Fleishman, Erica; Gibbons, David W.; Keim, Brandon; Lickorish, Fiona A.; Monk, Kathryn A.; Ockendon, Nancy; et al.
Highlights This is the sixth annual horizon scan. A team of 18 horizon scanners, researchers, and a journalist identified 15 issues following widespread consultation and a Delphi-like process to select the most suitable. The issues were wide ranging but included new sources of energy, novel pesticides, and underground gasification of coal.